2023
DOI: 10.1111/nph.18847
|View full text |Cite
|
Sign up to set email alerts
|

Multifeature analysis of age‐related microbiome structures reveals defense mechanisms of Populus tomentosa trees

Abstract: Root microbiota composition shifts during the development of most annual plants. Although some perennial plants can live for centuries, the host-microbiome partnerships and interaction mechanisms underlying their longevity remain unclear.To address this gap, we investigated age-related changes in the root metabolites, transcriptomes, and microbiome compositions of 1-to 35-yr-old Populus tomentosa trees.Ten co-response clusters were obtained according to their accumulation patterns, and members of each cluster … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 72 publications
0
19
0
Order By: Relevance
“…We noticed that several plant growth-promoting rhizobacterias (PGPRs) such as Actinobacteriota and Tumebacillus were highly abundant in the Turanga. These microbes have been reported to be associated with plant growth and stress responses 3,30,31 . The PGPR Bacillus, known for promoting plant growth through the production of hormone and nitrogen fixation, was found to be enriched in Aigeiros 32 .…”
Section: Taxonomic Features Of the Rhizosphere Microbial Composition ...mentioning
confidence: 99%
See 1 more Smart Citation
“…We noticed that several plant growth-promoting rhizobacterias (PGPRs) such as Actinobacteriota and Tumebacillus were highly abundant in the Turanga. These microbes have been reported to be associated with plant growth and stress responses 3,30,31 . The PGPR Bacillus, known for promoting plant growth through the production of hormone and nitrogen fixation, was found to be enriched in Aigeiros 32 .…”
Section: Taxonomic Features Of the Rhizosphere Microbial Composition ...mentioning
confidence: 99%
“…Rhizosphere microbial community structure is highly dynamic in part due to the changes in root exudation over the course of plant development [1][2][3][4] . Although some chemical signals released by plants facilitate specific interactions, many have been recognized by previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the composition of rhizosphere bacterial and fungal communities was influenced by the age of plant cultivation, a phenomenon documented in a limited number of cultivated crops such as mulberry, rice, and ginseng (Liu et al, 2016; Xiao et al, 2016; Tong et al, 2021). A recent study by Xie et al (2023) found that age‐related microbiome structures are related to the defence mechanisms of Populus tomentosa trees. Continuous cultivation of American ginseng ( Panax quinquefolius ) resulted in decreased bacterial diversity and increased fungal diversity in the soils compared to those used for traditional crops (Dong et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the composition of rhizosphere bacterial and fungal communities was influenced by the age of plant cultivation, a phenomenon documented in a limited number of cultivated crops such as mulberry, rice, and ginseng (Liu et al, 2016;Xiao et al, 2016;Tong et al, 2021). A recent study by Xie et al (2023) found that age-related microbiome structures are related to the defence mechanisms of Populus tomentosa trees.…”
mentioning
confidence: 99%
“…Although trees are long-lived perennials whose microbiota evolves over the course of their lives and the stage of forest cover (Xie et al, 2023), the initial assembly of the microbiota is thought to influence plant health and physiology (De Zelicourt et al, 2013; Dove et al, 2021; Mangeot-Peter et al, 2020). Previous studies have demonstrated that the microbiota of belowground and aboveground tissues of poplars ( Populus sp.)…”
Section: Introductionmentioning
confidence: 99%